Nitrogen environment, ecophysiology and growth of Gracilaria gracilus in Saldanha Bay, South Africa - Smit, Albertus Jacobus (University of Cape Town, 2016)
Bibliography: pages 132-157. === The growth of Gracilaria gracilis (Stackhouse) Steentoft, Irvine et Farnham was examined by studying the effect of organismic determinants such as thallus length, position along the thallus and branching in a series of in situ and laboratory-based experiments. Knowledge of these factors is essential in order to maximise production from suspended seaweed rafts seeded with vegetative G. gracilis fragments. Seeding netlons with freshly collected material provided up to 30 % higher relative growth rates than seaweed maintained on the netlons for three successive months. Initial seedstock length greatly affected growth rate and yield such that 30 cm thalli fragments resulted in growth rates 14 % higher than for 10 cm fragments. This difference is suggested to be due to higher contribution of growth by lateral branches to overall biomass. Comparisons of the growth of apical and basal fragments suggested that growth takes place over the entire length of the thallus but that the apex contributes more to overall elongation than does the proximal part. The removal of apical meristems resulted in an enhanced branching frequency with production of four times as many branches as intact fragments. Evidence is also provided for severe morphological differentiation following long periods of rapid growth. These thalli have very high frequency of branching, are hollow due to the disintegration of medullary cells and are considered to be completely senescent.